Workplace Learning: a New Technique for Continuing Education to LIS Professionals in Knowledge Society - Gadagin, B. R. (Journal of Information and Knowledge, 2012)
Changes are taking place in society, particularly in the area of higher education. The explosion of knowledge and information technology have virtually altered the characteristics of the learning environment, paving the way for new learning experiences. These drastic changes have impact on the Library and Information Science profession and leads to changes in the continuing education system for the LIS professionals. This article focuses on the role that workplace learning plays in the continuing education of LIS professionals, how they should go for workplace learning, what they have to learn, the necessity and the conditions for workplace learning etc.